2018
DOI: 10.1177/0003319718757615
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Peripheral Arterial Disease in Patients With Abdominal Aortic Aneurysm: A Retrospective Cohort Study (Version 5)

Abstract: Studies evaluating the risk of peripheral arterial disease (PAD) in patients with abdominal aortic aneurysm (AAA) are limited. We used insurance claims data of Taiwan to establish a cohort of 6590 patients with AAA newly diagnosed from 2000 to 2008 and 6590 controls without AAA matched by propensity score. The subsequent incidence density rates of PAD were estimated in both cohorts by the end of 2011, and the AAA cohort to the non-AAA cohort hazard ratios (HRs) of PAD were calculated using Cox proportional haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Besides the association between AAAs and PAD reported by Lin et al, 1 there is a strong association between AAAs and several other diseases, both CVD and non-CVD, such as cancer, periodontitis, CKD, SLE, COPD, and organ transplantation. It is important for physicians to be aware of these associations so that they have a higher index of suspicion for the early detection and timely management of AAAs in patients with these conditions.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Besides the association between AAAs and PAD reported by Lin et al, 1 there is a strong association between AAAs and several other diseases, both CVD and non-CVD, such as cancer, periodontitis, CKD, SLE, COPD, and organ transplantation. It is important for physicians to be aware of these associations so that they have a higher index of suspicion for the early detection and timely management of AAAs in patients with these conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Abdominal aortic aneurysms share the same vascular risk factors with these diseases (eg, smoking, hyperlipidemia, and hypertension). 5,6 Furthermore, atherosclerosis is a systemic disease, and the concomitant manifestation of arterial disease in >1 arterial bed is not unusual 5,6 ; the study by Lin et al 1 confirms this association.…”
Section: Abdominal Aortic Aneurysms and Vascular Disease In Other Artmentioning
confidence: 85%
See 2 more Smart Citations
“… 52 Lin et al recently published data on 6590 people with AAA, and found an increased risk of developing PAD in this cohort. 53 …”
Section: Discussionmentioning
confidence: 99%